ESTIMASI KEBUTUHAN SARANA DAN PRASARANA INTEGRASI MODA KSPN BOROBUDUR DI PALBAPANG (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
To support the Borobudur-Yogyakarta-Prambanan Super Priority KSPN (National Tourism Strategic Area) set by the Indonesian government in 2020, the Palbapang smart pavilion will be built, reactivation of railroad tracks and construction of the Palbapang Train Station to increase accessibility to Borobudur tourism objects. The Directorate General of Land Transportation plans to build an Intermodal Integration Terminal to integrate the four main objects and other surrounding objects. Through the First mile-Last mile approach of tourist trips to the Borobudur KSPN, the four-step transportation model, and the overlapping method of various existing plans, taking into account specific building regulations for the Borobudur KSPN area, the types and estimates of the amount of infrastructure and transportation needs needed for integration are generated modes such as the location of the intermodal terminal, the number of bus fleets, public and private transport routes, bus stops, parking spaces, and other supporting facilities. ABSTRAK Untuk mendukung KSPN (Kawasan Strategis Pariwisata Nasional) Super Prioritas Borobudur-Yogyakarta-Prambanan yang ditetapkan pemerintah RI pada tahun 2020, akan dibangun Anjungan cerdas Palbapang, reaktivasi jalur KA dan pembangunan Statsiun KA Palbapang untuk meningkatkan aksesibilitas ke obyek wisata Borobudur. Untuk mengintegrasikan ke empat obyek utama dan obyek-obyek lain di sekitarnya, Ditjen Perhubungan Darat berencana membangun Terminal Integrasi Antarmoda. Melalui pendekatan First mile-Last mile perjalanan wisata ke KSPN Borobudur, dan fourstep model transportasi serta metoda tumpang susun dari berbagai perencanaan yang sudah ada, dengan memperhatikan peraturan khusus bangunan untuk wilayah KSPN Borobudur, dihasilkan jenis dan estimasi besarnya kebutuhan prasarana dan sarana transportasi untuk integrasi moda seperti lokasi terminal intermoda, jumlah armada bus, rute angkutan umum dan kendaraan pribadi, halte, ruang parkir dan fasilitas pendukung lainnya.